Problems for biomedical fluid mechanics and transport phenomena - Johnson, Mark (Cambridge University Press, 2014)
How does one deal with a moving control volume? What is the best way to make a complex biological transport problem tractable? Which principles need to be applied to solve a given problem? How do you know if your answer makes sense? This unique resource provides over two hundred well-tested biomedical engineering problems that can be used as classroom and homework assignments, quiz material and exam questions. Questions are drawn from a range of topics, covering fluid mechanics, mass transfer and heat transfer applications. Driven by the philosophy that mastery of biotransport is learned by practice, these problems aid students in developing the key skills of determining which principles to apply and how to apply them. Each chapter starts with basic problems and progresses to more difficult questions. Lists of material properties, governing equations and charts provided in the appendices make this a fully self-contained work. Solutions are provided online for instructors.